2016
DOI: 10.1523/jneurosci.1444-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 Activation in Preexisting Oligodendrocytes of Adult Mice Drives New Myelin Synthesis and Enhanced CNS Function

Abstract: Growing evidence shows that mechanisms controlling CNS plasticity extend beyond the synapse and that alterations in myelin can modify conduction velocity, leading to changes in neural circuitry. Although it is widely accepted that newly generated oligodendrocytes (OLs) produce myelin in the adult CNS, the contribution of preexisting OLs to functional myelin remodeling is not known. Here, we show that sustained activation of extracellular signal-regulated kinases 1 and 2 (ERK1/2) in preexisting OLs of adult mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 74 publications
5
78
0
Order By: Relevance
“…The major outcomes of the loss‐ and gain‐of‐function studies on the roles of mTORC1 and the upstream PI3K‐Akt and Mek‐Erk1/2 pathways in PNS and CNS myelination are summarized (Beirowski et al, 2017; Bercury et al, 2014; Carson et al, 2015; Cotter et al, 2010; Domenech‐Estevez et al, 2016; Figlia et al, 2017; Flores et al, 2008; Fyffe‐Maricich, Karlo, Landreth, & Miller, 2011; Fyffe‐Maricich, Schott, Karl, Krasno, & Miller, 2013; Goebbels et al, 2010, 2012; Ishii, Furusho, & Bansal, 2013; Ishii, Furusho, Dupree, & Bansal, 2016; Jeffries et al, 2016; Jiang et al, 2016; Lebrun‐Julien et al, 2014; Napoli et al, 2012; Newbern et al, 2011; Norrmén et al, 2014; Sheean et al, 2014; Sherman et al, 2012; Wahl et al, 2014; Zou et al, 2011, 2014)…”
Section: Myelination and Mtormentioning
confidence: 99%
“…The major outcomes of the loss‐ and gain‐of‐function studies on the roles of mTORC1 and the upstream PI3K‐Akt and Mek‐Erk1/2 pathways in PNS and CNS myelination are summarized (Beirowski et al, 2017; Bercury et al, 2014; Carson et al, 2015; Cotter et al, 2010; Domenech‐Estevez et al, 2016; Figlia et al, 2017; Flores et al, 2008; Fyffe‐Maricich, Karlo, Landreth, & Miller, 2011; Fyffe‐Maricich, Schott, Karl, Krasno, & Miller, 2013; Goebbels et al, 2010, 2012; Ishii, Furusho, & Bansal, 2013; Ishii, Furusho, Dupree, & Bansal, 2016; Jeffries et al, 2016; Jiang et al, 2016; Lebrun‐Julien et al, 2014; Napoli et al, 2012; Newbern et al, 2011; Norrmén et al, 2014; Sheean et al, 2014; Sherman et al, 2012; Wahl et al, 2014; Zou et al, 2011, 2014)…”
Section: Myelination and Mtormentioning
confidence: 99%
“…Furthermore, we have shown that FGFR and ERK-MAPK signaling continues to be required in oligodendrocytes throughout adulthood for the long-term growth and maintenance of myelin and for the support of axonal integrity (Ishii et al, 2014). In addition, when ERK1/2 are activated in preexisting mature oligodendrocytes during adulthood, new myelin growth can be reinitiated, even after active myelination is terminated, which has important implications for understanding the mechanism underlying the plasticity of myelin in adult life (Ishii et al, 2016;Jeffries et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, small GTPases of the Rho family intervene in the Erk1/2 signaling cascade and a recently published study uncovered a direct relation of Vav3 and Erk1/2 signaling in a gastric cancer cell line (Tan et al, 2016). In contrast, Erk1/2 signaling is involved in CNS myelination and remyelination (Gonsalvez, Ferner, Peckham, Murray, & Xiao, 2016;Guardiola-Diaz, Ishii, & Bansal, 2012;Jeffries et al, 2016). Therefore, a differential phosphorylation of Erk1/2 in Vav3 −/− OLs could be possible.…”
Section: Discussionmentioning
confidence: 99%